2019
DOI: 10.1108/apjml-09-2018-0383
|View full text |Cite
|
Sign up to set email alerts
|

Can corporate philanthropy change consumers’ perceptions of Japanese multinationals and reduce animosity toward them?

Abstract: Purpose The purpose of this paper is to empirically investigate how corporate philanthropy (CP) can affect consumer perceptions of Japanese multinationals, for which there exists strong animosity in Asia, and how this animosity can be attenuated. Design/methodology/approach The study first examines Japanese firms in China (Study 1) and then Japanese, European and local firms in Korea (Study 2). Findings The results suggest that CP activities can have a positive effect on the consumer recognition of company… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…This negative feeling in turn may reduce their intention to purchase Japanese products, even if they are perceived as being high in quality (Klein et al , 1998). Other studies have also investigated Chinese consumers' animosity that is grounded on conflicts with other countries as affecting purchase decisions (Han et al , 2020, 2021; Souiden et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This negative feeling in turn may reduce their intention to purchase Japanese products, even if they are perceived as being high in quality (Klein et al , 1998). Other studies have also investigated Chinese consumers' animosity that is grounded on conflicts with other countries as affecting purchase decisions (Han et al , 2020, 2021; Souiden et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Different industry features might generate different effects on consumer evaluations. Finally, future research on ethnocentrism can be targeted at different countries or groups (Han et al , 2019). Hamin et al (2014) found ethnocentrism influence customers' preference for their own latecomer brands in the emerging markets.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research has debated possible reasons why companies engage in CSR. Prior research indicates that most firms implement CSR initiatives to enhance reputation (Chernev and Blair, 2015;Ellen et al, 2006), co-creation behavior (Yoon and Lee, 2019) or to positively influence corporate image (Han et al, 2019), consumer brand attitudes or brand choice (Vanhamme et al, 2012).…”
Section: Theoretical Background Csr Activity Of Luxury Brandsmentioning
confidence: 99%